Performance of Malaysian journals in MyCite 2013 (Pusat Sitasi Malaysia, 2014)
As part of the Malaysian Citation Centre (MCC) assessment exercise, a bibliometrics analysis of Malaysian scholarly publications was conducted in 2014 to produce the second report of Malaysian journals performance. The data reported here are as at October 2014 and were compiled solely from MyJurnal and MyCite databases. The analysis was based on the journals that are fully indexed from the years 2008 to 2013 by the MCC, currently based at the Department of Higher Education, Ministry of Education, Malaysia.This report applies the bibliometric method and uses datasets which comprise articles published in 129 Malaysian journals and citations to the 22,926 articles published in these journal. The performance indicators include journals publication productivity, the citations they garner, and their scores on other bibliometric indices such as journal impact factor (IF), h-index, cited half-life and immediacy index. This datasets are used to evaluate publication productivity and impact to highlight research disciplines, persons and institutions of excellence.